Determinación de metales pesados en especies vegetales de una área explotada por la minería aurífera en el sector de La Pangui-Zamora Chinchipe - Armijos Armijos, Karina. (2015)
This research was performed in mining area “La Pangui” located in Zamora Chinchipe Province, from January to July 2014, in order to identify the existence and concentration of heavy metals the like Cu, Pb, Fe, Cd, Hg in plant species. The Fieldwork considers three investigation areas that are: a Natural Zone (ZN), Intervened Zone (ZI) and a Recovery Zone (ZR). The concentration of heavy metals in plant species, was determined by atomic absorption spectrophotometry. Values for heavy metals were found in different plant´s parts like: leaves, stem and roots. Also, could be determined bioacumuladoras species, such as: family of Cyatheaceae (tortuous Cyathea), Melastomataceae (Miconia sp), Apocynaceae (Mandevilla pedicure) and Poaceae (Pennisetum peruvianum), It could be used for soils phytoremediation.